EARLY HISTOPATHOLOGICAL COMPARISON OF SINGLE VERSUS DOUBLE-LAYER CLOSURE OF UTERINE INCISION DURING CESAREAN: A CONTROLLED STUDY IN RATS - Merve Civelek; Selim Büyükkurt; Mehmet Bertan Yılmaz; Kıvılcım Eren Erdoğan; Hale Öksüz; Çağrı Avcı; Gülşah Seydaoğlu (İstanbul Tıp Fakültesi Dergisi)
Objective: Long-term complications of cesarean delivery are numerous and are increasing due to the high cesarean rate. The long-term complications are attributed to the different suturing methods. The single-layer locked (SLL) and double-layerunlocked (DLU) are the most compared. This study aims to compare the early histopathological properties of these two suture techniques in an experimental animal study.Material and Method: Ten pregnant Wistar-Albino rats had cesarean at term. The right uterine horns were repaired using the SLL suture technique, and the left ones were repaired using the DLU technique. The control subjects were the six uterine horns of three pregnant rats delivered vaginally. Each animal underwent a hysterectomy on day 15 of pregnancy, and each uterus was an experimental unit. The mean thickness of the endometrium and myometrium of the intervention groups with histopathological features and controls were compared.Result: In SLL and DLU groups, the endometrium (276.6±123.1vs. 258.4±125.9 μm; p=0.748) and myometrium (531.7±189.2 vs. 505.9±182.1 μm; p=0.612) in scarred areas were similar. In nonscarred areas, the endometrium was measured as 239.9±68.9, 256.5±127.2, and 316.4±98.6 μm in SLL, DLU, and control group, respectively (p=0.347). The myometrium of non-scarred areas was also similar in all groups evaluated (387.2±119.9; 364.5±154.1 and 234.0±49.1 μm; p=0.265). The histopathological features of uteri repaired with two different techniques were also similar.Conclusion: The early histopathological properties of all uteri examined were similar after repairing with SLL or DLU techniques. These results indicate that the repair process does not differ in the early stages, regardless of the uterine closure technique used.